Pengaruh Brand Personality, Brand Experience, Self-Brand Connection, Brand Love & Brand Trust terhadap Brand Loyalty Kosmetik Wardah - Juniarty Siahaan; Thalia Nevita Marchelin; Cynthia Anna Wijayanti (Journal of Management and Business Review, 2023)
Technological advances sharpen competition in the cosmetics industry and force companies to innovate to stay competitive continuously. The study aims to test and analyze the influence of brand personality, brand experience, self-brand connection, brand love brand trust on the brand loyalty of Wardah Cosmetics users. This research proposes a modified research model from the previous research model, which is expected to produce a model that can predict Brand Loyalty through empirical research in the cosmetic industry. Primary data was collected from 402 Indonesian female respondents who became Wardah customers before 2021 with a non-probability purposive sampling technique. Model construction and its interrelationships were tested with partial least square-structural equation modeling (PLS-SEM) using SmartPLS 3.3.2 program. The result shows that brand personality positively affects brand experience and self-brand connection, and brand personality and brand experience affect brand love. More, brand trust, self-brand connection, brand love, and brand trust positively affect brand loyalty. The novelty proposed is the empirical research model that has never been used in predicting brand loyalty in Wardah cosmetic products, and expectedly other companies can also use this model in developing marketing strategies to increase their brand loyalty.